Boys in court :|questioning child abuse cases between 1860 and 1865 - Oruçoğlu, Erkan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis explores how the sexual offenses committed against the male children were handled by the Ottoman courts and the society at large in the Ottoman lands between the years 1860 and 1865 together with the regulations drafted and implemented in the Ottoman reform period. As the study comprehensively analyzes the court cases in which numerous male children and their families stood as victims of sexual crimes and which were referred to Meclis-i Vâlâ-yı Ahkâm-ı Adliye, the official council formed to serve as the Supreme Court for legal matters and an ultimate court of appeals. This thesis reveals significant points regarding the court practices, interrogation methods, the concept of childhood and how the social and cultural codes were reflected on the court proceedings as well as the relations between the individual and state reshaped under the Tanzimat regulations and the relations between the center and the periphery.
Keywords: Child sexual abuse -- Turkey.; Boys -- Abuse of -- Turkey.